Repo intermediation and central clearing: An analysis of sponsored repo - Adam Copeland; R. Jay Kahn (Federal Reserve Bank of New York, 2024)
This paper evaluates the salient forces behind a dealer-intermediary's decision to move a bilateral repo transaction with a customer into central clearing. We provide evidence that dealers turn to sponsored repo on occasions when balance sheet space is scarce, such as when there is a large issuance of Treasury coupon securities and end-of-month dates. We also find that sponsored repo spreads tend to be affected by a range of factors, with the three largest drivers being money market fund assets, a proxy for hedge fund demand for repo funding, and end-of-month dates.
Keywords: G12; G23; 330; repo; sponsored services; central clearing; money markets